Added Value for Waste Veneer through the Engineered Wood Products Method (Bended chair) for Eucalyptus Hybrid - syvongsouk, khonexai (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research utilized K7 eucalyptus wood-veneer waste from plywood production. Poor-quality veneer, which cannot be used for high-value applications, accounts for approximately 30–40% of total production and becomes waste. Therefore, it is important to explore methods for transforming this waste into innovative and value-added wood products. The objective of this study was to evaluate the strength of bent K7 veneer waste in order to design wood products suitable for specific applications and to determine the load-bearing capacity of veneer wood in different dimensions. The veneer material was sourced from PML Easbeam Industrial Co., Ltd., located at 450 Road, Chom Si Village, Xaysetha District, Vientiane Capital. The veneer sheets were cut to dimensions of 2.4 × 40 × 2400 mm, dried to a moisture content of 6–8%, processed with a moulder, mixed with adhesive, pressed, cut to the required sizes, and tested as plywood in 5-ply, 7-ply, 9-ply, and 11-ply configurations. The results show that eucalyptus (K7) veneer waste can be effectively transformed into cost-efficient, value-added products. In the plywood manufacturing process, the 5-ply panels used 25 grams of glue per sheet, the 7-ply panels used 32 grams, the 9-ply used 39 grams, and the 11-ply used 46 grams. Testing of bent veneer showed that load-bearing capacity increased with the number of layers, with the 11-ply plywood exhibiting the highest strength compared to configurations with fewer layers.